Bismuth-based mixed-anion compounds for anode materials in rechargeable batteries. Issue 20 (21st February 2022) - Kumar, Prashant; Wahyudi, Wandi; Sharma, Abhinav; Yuan, Youyou; Harrison, George T.; Gedda, Murali; Wei, Xuan; El-Labban, Abdulrahman; Ahmad, Shahzad; Kumar, Vinod; Tung, Vincent; Anthopoulos, Thomas D.
Abstract : Chemical composition control in ternary mixed-anion material bismuth sulfide iodide (Bi–S–I) is achieved by controlling the sulfide concentration. Synthesized BiSI and BiSI/Bi13 S18 I2 show promise as anode materials for lithium-ion batteries. Abstract : A facile solvothermal synthesis approach for chemical composition control in ternary Bi–S–I systems is reported by simply controlling the sulfide concentration. We demonstrate the application of these bismuth-based ternary mixed-anion compounds as high capacity anode materials in rechargeable batteries. Cells utilising Bi13 S18 I2 achieved an initial capacity value of 807 mA h g −1, while those with BiSI/Bi13 S18 I2 a value of 1087 mA h g −1 in lithium-ion battery systems.